The sands of Sea Blue Beach - Hauck, Rachel, 1960- (Bethany House, a division of Baker Publishing Group, 2025)
"Highschool sweethearts Emery Quinn and Caleb Ransom both return to Sea Blue Beach for a fresh start, but painful memories resurface, and they're faced with new challenges. As they each work to preserve the divided town, they take a chance at joining forces to reunite the division between old and new while rekindling love in the process"--